2016
DOI: 10.1590/2177-6709.21.5.047-052.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vertical placement angle on the insertion torque of mini-implants in human alveolar bone

Abstract: Objective: The aim of the present ex-vivo study was to evaluate the effect of the vertical placement angle of mini-implants on primary stability by analyzing maximum insertion torque (MIT). Methods: Mini-implants were placed in 30 human cadavers, inserted at either a 90° or 60° angle to the buccal surface of the maxillary first molar. Out of 60 self-drilling mini-implants used, half were of the cylindrical type and half were of the conical type. Primary stability was assessed by means of measuring the MIT. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
3
2
0
Order By: Relevance
“…At 90°, it increased to 16.249 MPa in stainless steel implant, whereas in titanium implant, it increased to 16.416 MPa. These findings are consistent with the finding of Maya et al 31 who, in their study, found that as the angle of insertion of mini-implant increases, the torque required to insert the implant also increases. Though theirs was a cadaver-based study, it can be postulated that as the insertion torque is increasing with the increase in the insertion angle, stress generated in the implant is also increasing.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At 90°, it increased to 16.249 MPa in stainless steel implant, whereas in titanium implant, it increased to 16.416 MPa. These findings are consistent with the finding of Maya et al 31 who, in their study, found that as the angle of insertion of mini-implant increases, the torque required to insert the implant also increases. Though theirs was a cadaver-based study, it can be postulated that as the insertion torque is increasing with the increase in the insertion angle, stress generated in the implant is also increasing.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are also in accordance with the findings of Maya et al 31 who used two types of mini-implants (cylindrical and conical); the maximum insertion torque for cylindrical implants at 60° was 14.13 MPa and at 90° was 17.27 MPa. On the other hand, the maximum insertion torque values for the conical mini implants were 11.40 Ncm for the 60° angle and 14.40 Ncm for the 90° angle.…”
Section: Discussionsupporting
confidence: 92%
“…Third, considering bone-mini-implant contact, the lingual surface of the mini-implant has more bone contact than the buccal surface, and there are more chances for the threaded portion of the mini-implant to get exposed and unsupported by the bone proper because of the excessive angulation of the mini-implant. This study and various previous studies[ 8 , 15 ] prove that an angle of insertion of 90° is recommended for better biomechanical stability as far as root damage is avoided.…”
Section: Discussionsupporting
confidence: 71%
“…Contrary to this study were the results of the study done by Wilmes B et al, Maya RR et al where they stated that mini-implants inserted at an angle of 900 displayed a greater insertion torque than the ones inserted at an angle of 600 and hence were less stable. 15,16 Keeping the other variables (material and angulation) constant, when the effect of length of mini-implants on its primary stability was compared, the results showed that on increasing the length of mini-implants, the stability of mini-implants increased for both the angulations. Congruent with this study was the work done by Petrey JS et al Kim YK et al, Mohammed HI et al, Chatzigianni A et al 4,17,18,19 Kim YK et al 17 stated that long mini-implant provides higher stability with higher torque during removal.…”
Section: Implant Angulationsmentioning
confidence: 99%